The EU Internal Market in Comparative Perspective Economic, Political and Legal Analyses - Hanf, Dominik; Hanf, Dominik; Chang, Michele; Pelkmans, Jacques (Peter Lang, 2012)
The European Union$1 (Bs internal market is the (S0(Bhard core(S1 (Bof integration and by far its most precious asset. However a number of deep-seated factors have impeded the development of a systematic and wide-ranging academic research programme dedicated to the internal market. The purpose of this book is to begin to address this predicament with a tri-disciplinary analysis of the internal market, as scant opportunities for mutual understanding and learning across disciplines (law, economics and politics) currently exist. Internal market scholars from all three disciplines collaborated on this project, in which each chapter was read and critiqued by a scholar from a different discipline. The editors trust that this unique exercise reveals to many readers the enormous potential for in-depth and continuous analysis of the internal market and all that it entails. It also provides an accessible text for students and scholars from all three disciplines interested in the internal market.s